2011
DOI: 10.1007/s10067-011-1827-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower gastrointestinal perforation in rheumatoid arthritis patients treated with conventional DMARDs or tocilizumab: a systematic literature review

Abstract: Tocilizumab, a monoclonal antibody targeting the IL-6 receptor, has recently been added to the therapeutic armamentarium against rheumatoid arthritis (RA). Despite its overall safety, concerns have been raised regarding diverticular perforation in patients receiving the drug. The aim of our research was to document the incidence of diverticular disease in RA patients treated in the pre-disease-modifying anti-rheumatic drug (DMARD) era, following treatment with conventional DMARDs, and subsequent to tocilizumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 23 publications
2
64
0
4
Order By: Relevance
“…Lower GI perforations are rare, but serious complications of TCZ treatment appear to occur more frequently in patients receiving glucocorticoids 15 . The overall incidence of GI perforation in our study was comparable with reports from longterm extensions of TCZ randomized trials and did not increase over time 8 .…”
mentioning
confidence: 99%
“…Lower GI perforations are rare, but serious complications of TCZ treatment appear to occur more frequently in patients receiving glucocorticoids 15 . The overall incidence of GI perforation in our study was comparable with reports from longterm extensions of TCZ randomized trials and did not increase over time 8 .…”
mentioning
confidence: 99%
“…IL-6 is a key driver of the features of inflammation and reports suggest that the use of tocilizumab is associated with suppression of temperature and acute phase response (Hirao et al 2009). In addition, there has been a concern regarding gastro-intestinal perforation, and review by us (Gout et al 2011) has revealed that the risk is similar to that of anti-TNF agents but way below that for corticosteroids. IL-6 inhibition is also associated with reversible neutropenia, abnormalities of the lipid profile and transient elevation of liver enzymes, therefore, studies are looking at the medium and long-term implications of these findings.…”
Section: Interleukin 6 Inhibitionmentioning
confidence: 94%
“…Bu ilac› alan bir hastada yeni ortaya ç›kan kar›n a¤r›s› varl›¤›nda bu olas›l›k akla gelmelidir. [6,48] • Maligniteler: Malignite görülme s›kl›¤› 100 hasta y›-l› için, tüm maligniteler aç›s›ndan 1.1, sadece nonmelanom deri kanseri için 0.3, solid organ kanserleri için 0.7 ve lenfoma gibi hematolojik maligniteler için 0.1 olarak bildirilmifltir. TCZ kullan›m süresi uzad›k-ça, malignite görülme s›kl›¤› artmamaktad›r.…”
Section: Il-1 Tedavisinin Yan Etkileri Nelerdir?unclassified